Characterizations of novel broad-spectrum lytic bacteriophages Sfin-2 and Sfin-6 infecting MDR Shigella spp. with their application on raw chicken to reduce the Shigella load - Ahamed, S. K. Tousif; Rai, Srijana; Guin, Chiranjib; Jameela, Rameez Moidu; Dam, Somasri; Muthuirulandi Sethuvel, Dhiviya Prabaa; Balaji, V.; Giri, Nabanita (Frontiers in Microbiology, 2023)
The evidence and prevalence of multidrug-resistant (MDR) Shigella spp. poses a serious global threat to public health and the economy. Food- or water-borne MDR Shigella spp. demands an alternate strategy to counteract this threat. In this regard, phage therapy has garnered great interest from medical practitioners and researchers as a potential way to combat MDR pathogens. In this observation, we isolated Shigella phages from environmental water samples and tested against various clinically isolated MDR Shigella spp. In this study, we have defined the isolation and detailed physical and genomic characterizations of two phages Sfin-2 and Sfin-6 from environmental water samples. The phages exhibited potent lytic activity against Shigella flexneri, Shigella dysenteriae, and Shigella sonnei. They showed absorption within 5–10 min, a burst size ranging from ~74 to 265 PFU/cell, and a latent period of 5–20 min. The phages were stable at a broad pH range and survived an hour at 50°C. The purified phages Sfin-2 and Sfin-6 belong to the Siphoviridae family with an isometric head (64.90 ± 2.04 nm and 62.42 ± 4.04 nm, respectively) and a non-contractile tail (145 ± 8.5 nm and 148.47 ± 14.5 nm, respectively). The in silico analysis concluded that the size of the genomic DNA of the Sfin-2 phage is 50,390 bp with a GC content of 44.90%, while the genome size of the Sfin-6 phage is 50,523 bp with a GC content of 48.30%. A total of 85 and 83 putative open reading frames (ORFs) were predicted in the Sfin-2 and Sfin-6 phages, respectively. Furthermore, a comparative genomic and phylogenetic analysis revealed that both phages represented different isolates and novel members of the T1-like phages. Sfin-2 and Sfin-6 phages, either individually or in a cocktail form, showed a significant reduction in the viable Shigella count on raw chicken samples after 72 h of incubation. Therefore, these results indicate that these phages might have a potential role in therapeutic approaches designed for shigellosis patients as well as in the biological control of MDR Shigella spp. in the poultry or food industry during the course of meat storage.